Subsidies: The Distorted Economics of Biofuels - Steenblik, Ronald (OECD/ITF Joint Transport Research Centre Discussion Papers, 2007)
Governments have influenced the development of bioenergy, particularly liquid biofuels (ethanol, biodiesel and pure plant oil used as a fuel), for several decades. This paper discusses the economics of biofuels and provides an overview of current policy measures to support their production and consumption. It discusses also how the different policies supportive of biofuels interact with broader agricultural, energy, environmental and transport policies, and the relative effectiveness of biofuels in achieving objectives in these areas. The paper concludes with several recommendations on further research